2015
DOI: 10.1111/mec.13203
|View full text |Cite
|
Sign up to set email alerts
|

Positive and purifying selection in mitochondrial genomes of a bird with mitonuclear discordance

Abstract: Diversifying selection on metabolic pathways can reduce intraspecific gene flow and promote population divergence. An opportunity to explore this arises from mitonuclear discordance observed in an Australian bird Eopsaltria australis. Across >1500 km, nuclear differentiation is low and latitudinally structured by isolation by distance, whereas two highly divergent, parapatric mitochondrial lineages (>6.6% in ND2) show a discordant longitudinal geographic pattern and experience different climates. Vicariance, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
159
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(174 citation statements)
references
References 112 publications
13
159
2
Order By: Relevance
“…Thousands of studies have been based solely on mtDNA and the question has arisen as to whether the results of such studies can be accepted or whether they must be tested by corresponding analyses of nuclear loci. In our opinion, a relatively few instances of discordance between mitochondrial and nuclear genes has been emphasized [41][42][43], despite more frequent cases of congruence between the two types of markers [2,8,44 -46]. Our systematic examinations suggest that mtDNA can be an efficient estimator of population divergence, but not effective population size, which requires multiple loci for accurate estimate [2,8].…”
Section: Discussionmentioning
confidence: 76%
“…Thousands of studies have been based solely on mtDNA and the question has arisen as to whether the results of such studies can be accepted or whether they must be tested by corresponding analyses of nuclear loci. In our opinion, a relatively few instances of discordance between mitochondrial and nuclear genes has been emphasized [41][42][43], despite more frequent cases of congruence between the two types of markers [2,8,44 -46]. Our systematic examinations suggest that mtDNA can be an efficient estimator of population divergence, but not effective population size, which requires multiple loci for accurate estimate [2,8].…”
Section: Discussionmentioning
confidence: 76%
“…Additional support for the hypothesis has been provided from studies of other metazoans, some of which have reported signatures of positive selection on mtDNA genes sampled from populations inhabiting particular thermal environments (Foote, et al 2011;Silva, et al 2014;80 Ma, et al 2015;Morales, et al 2015), and others which have documented variation in mitochondrial gene or haplotype frequencies along clinal gradients associated with climate, such as latitude (Silva, et al 2014;Consuegra, et al 2015), altitude (Fontanillas, et al 2005; Cheviron and Brumfield 2009), or with temperature itself (Quintela, et al 2014). Such clinal patterns are, however, based on correlations between haplotype frequencies and 85 environmental gradients.…”
Section: Introductionmentioning
confidence: 97%
“…However, despite a background of strong purifying selection, particular sites in the mitochondrial genome can experience positive selection in response to environmental pressures. Many studies have reported positive selection acting on mitochondrial protein-coding genes in vertebrates in response to environmental factors, including in mammals (da Fonseca et al, 2008), birds (Stager et al, 2014;Morales et al, 2015) and fish (Silva et al, 2014). Many of these studies find that candidate sites for positive selection are disproportionately concentrated in the NADH complex genes (OXPHOS complex I), which produces~40% of the proton flux required for ATP synthesis (Garvin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%